Physiological and performance adaptations of elite Greco-Roman wrestlers during a one-day tournament - Barbas, I.; Fatouros, I. G.; Douroudos, I. I.; Chatzinikolaou, A.; Michailidis, Y.; Draganidis, M.; Jamurtas, A. Z.; Nikolaidis, M. G.; Parotsidis, C.; Theodorou, A. A.; Katrabasas, I.; Margonis, K.; et al. (European Journal of Applied Physiology, 2011)
The aim of this study was to determine the effects of a simulated one-day Greco-Roman wrestling tournament on selected performance and inflammatory status indices. Twelve competitive wrestlers (22.1 ± 1.3 years) completed five matches according to the official Olympic wrestling tournament regulations following a ~6% weight loss. Performance measurements, muscle damage assessment, and blood sampling were performed before and following each match. Performance and inflammatory markers were not affected by weight loss. Mean wrestling heart rate reached ~85% of maximal and lactate concentration exceeded 17 mM. Fatigue rating demonstrated a progressive rise (P < 0.05) throughout the tournament, peaking in match 4. Performance demonstrated a progressive deterioration (P < 0.05) throughout the tournament, especially in the last two matches (P < 0.05), with upper-body measures exhibiting a greater decline (P < 0.05) and remaining below baseline (P < 0.05) until the end of the tournament. Muscle damage markers increased during the course of the tournament with upper limbs affected more. Creatine kinase activity, CRP levels, IL-6 concentration, and leukocyte counts increased (P < 0.05) progressively throughout the tournament, peaking in the last two matches. Cortisol, epinephrine and norepinephrine increased (P < 0.05) after each match, but testosterone declined (P < 0.05) progressively, reaching a nadir before the last match. This inflammatory response was accompanied by a marked increase (p < 0.05) in lipid peroxidation, protein oxidation, and antioxidant status markers indicating the development of oxidative stress. These results suggest that a one-day wrestling tournament may induce significant physiological demands on wrestlers that may adversely affect their performance and inflammatory status especially during the later stages of the tournament.